ПОЗДНЕЧЕТВЕРТИЧНЫЕ МОРСКИЕ ТЕРРАСЫ В ПРИБРЕЖНОЙ ЗОНЕ ЯПОНСКОГО МОРЯ (СЕВЕРО-ЗАПАДНЫЙ СЕКТОР) - Короткий A.M. (My University, 2005)
Three phases of sea level rise exceeding recent level by 6-10 m are recorded in the deposits of three marine terraces (with the heights up to 12-15 m) at the continental coast of the Japan Sea. Thermoluminiscent dates, spore-pollen and diatomic complexes of these terraces allow us to compare transgressions with stage 5e and last episodes ol the stage 5c. The wide occurrence of coastal deposits with moderate-cold pollen complexes above recent sea level was established. This fact contradicts the apprehension that peaks of transgression coincide only with warm climate phases of Pleistocene. Our results are confirmed by A.N. Molodkov who proved that during 130-75 ma there hac been a transgression with insignificant fluctuations of ocean level.
Keywords: Pleistocene; 551.435.322(265.54); Cenozoic::Quaternary::Pleistocene